(untitled) (Fiep Bulletin - online, 2014)
The civil-military articulation responsable for the coup d’état of 1964 guided their actions around the implantation of a conservative societary project that sought the elimination of the political dissent. In the education field, this strategy implicated the promulgation of a group of laws imbued with an authoritarian and disarmer character. This way, the objective of this article is centered in the analysis of the education politics returned to the higher education, privileging the attributed role to the Physical education. For this, a methodology used was based in the bibliographical research and analytical categories that aid to unmask the ideology and strategies put in practice in this reform. It was verified that the education was reformulated in consonance with the business model and the imposition of discipline through the teaching. In this context, the Physical education was used as repression and diffusion mechanism of a favorable ideology to the military regime.